The optimal inflation target: Bridging the gap between theory and policy - Klaus Adam; Henning Weber (Deutsche Bundesbank, 2024)
Many central banks worldwide announce numerical inflation targets, typically ranging from zero to two percent in advanced economies and higher in developing countries. Historically, a significant gap existed between the inflation targets pursued by central banks and those recommended by academic studies. This paper reviews traditional economic forces advocating for zero or negative inflation targets and surveys new forces justifying positive targets. Key factors include (i) trends in relative prices, (ii) the lower bound constraint on nominal interest rates, (iii) (downward) wage rigidity, and (iv) effects of product entry and aggregation. By examining these forces, we assess whether current inflation targets are optimal or require adjustment, and identify areas for future research on optimal inflation targets.
Keywords: E31; E52; E58; 330; Optimal inflation rate; relative price trends; effective lower bound; nominal rigidities; product aggregation